Pediatric Residents and Interns in an Italian Hospital Perform Improved Bibliographic. A Review of: Gardois, P., Calabrese, R., Colombi, N., Lingua, C., Longo, F., Villanacci, M., Miniero, R., & Piga, A. (2011). Effectiveness of bibliographic searches performed by paediatric residents and interns assisted by librarian. A randomised controlled trial. Health Information and Libraries Journal, 28(4), 273-284. doi: 10.1111/j.1471-1842.2011.00957.x - Mathew Stone (Evidence Based Library and Information Practice, 2013)
Objective – To establish whether the assistance of an experienced biomedical librarian delivers an improvement in the searching of bibliographic databases as performed by medical residents and interns. Design – Randomized controlled trial. Setting – The pediatrics department of a large Italian teaching hospital. Subjects – 18 pediatric residents and interns. Methods – 23 residents and interns from the pediatrics department of a large Italian teaching hospital were invited to participate inthis study, of which 18 agreed. Subjects were then randomized into two groups and asked to spend between 30 and 90 minutes searching bibliographic databases for evidence to answer a real-life clinical question which was randomly allocated to them. Each member ofthe intervention group was provided with an experienced biomedical librarian to provide assistance throughout the search session. The control group received no assistance. The outcome of the search was then measured using an assessment tool adapted for the purpose of this study from the Fresno test of competence in evidence based medicine. This adapted assessment tool rated the “global success” of the search and included criteria such as appropriate question formulation, number of PICO terms translated into search terms, use of Boolean logic, use of subject headings, use of filters, use of limits, and the percentage of citations retrieved that matched a gold standard set of citations found in a prior search by two librarians (who were not involved in assisting the subjects) together with an expert clinician. Main Results – The intervention group scored a median average of 73.6 points out of a possible 100, compared with the control group which scored 50.4. The difference of 23.2 points in favour of the librarian assisted group was a statistically significant result (p value = 0.013) with a 95% confidence interval of between 4.8 and 33.2. Conclusion – This study presents credible evidence that assistance provided by an experienced biomedical librarian improves the quality of the bibliographic database searches performed by residents and interns using real-life clinical scenarios.